Rapid weight-loss impairs simulated riding performance and strength in jockeys: implications for making-weight - Wilson, G.; Hawken, M. B.; Poole, I.; Sparks, A.; Bennett, S.; Drust, B.; Morton, J.; Close, G. L. (Journal of Sports Sciences, 2014)
Despite the performance concerns of dehydration in other sports, there are currently no data on the effects of rapid weight-loss on the physical and cognitive performance of jockeys in a sport-specific context. In a randomised crossover design, eight Great Britain (GB) male licensed jockeys were assessed for chest strength, leg strength, simulated riding performance (assessed by maximum pushing frequency on a mechanical riding simulator during the final two furlongs of a simulated 2 mile race) and simple reaction time after performing 45 min of exercise, during which euhydration was maintained (Control trial) or induced 2% dehydration (Rapid Weight-Loss trial). Reductions in both chest (-13.8 ± 3.03% vs. 0.62 ± 1.04%) and leg strength (-4.8 ± 4.8% vs. -0.56 ± 2.5%) were greater in Rapid Weight-Loss compared with Control (P < 0.01 and P = 0.04, respectively). Similarly, reductions in simulated riding performance were also greater (P = 0.05) in Rapid Weight-Loss (-2.8 ± 4.0%) compared with Control (-0.07 ± 1.5%), whereas there were no significant changes (P = 0.14) in simple reaction time. We conclude that a 2% reduction in body mass, as achieved by 45 min of moderate-intensity exercise undertaken in a sweatsuit (a common method of inducing acute dehydration by jockeys), significantly impairs maximum pushing frequency during a simulated race. In addition, the observed reductions in strength may also increase the occupational hazards associated with race riding.